1997
DOI: 10.1159/000121208
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Herniation of the Hindbrain in Craniosynostosis

Abstract: The occurrence and extent of herniation of the hindbrain has been evaluated in a population of children with craniosynostosis by means of magnetic resonance imaging of the craniocervical junction. The role of intracranial pressure (ICP), posterior fossa size and hydrocephalus in the development of this deformity has also been assessed. Magnetic resonance imaging (Siemens Magnetom 1.5T) was reviewed in 27 cases of craniosynostosis in whom there had been no previous cranial vault surgery. The position of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 25 publications
(37 reference statements)
2
27
0
Order By: Relevance
“…The tonsillar herniation observed in patients with syndromic craniosynostosis has also been attributed to a normal-sized cerebellum in a hypoplastic posterior fossa further compromised by premature closure of the lambdoid suture [4, 6]. In our study, premature closure of the lambdoid suture was related to more severe degrees of venous outflow obstruction by MRV, suggesting the same forces causing premature closure of the lambdoid sutures may also affect the jugular foramen.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The tonsillar herniation observed in patients with syndromic craniosynostosis has also been attributed to a normal-sized cerebellum in a hypoplastic posterior fossa further compromised by premature closure of the lambdoid suture [4, 6]. In our study, premature closure of the lambdoid suture was related to more severe degrees of venous outflow obstruction by MRV, suggesting the same forces causing premature closure of the lambdoid sutures may also affect the jugular foramen.…”
Section: Discussionsupporting
confidence: 58%
“…The intra-cranial manifestations of chronic mildly elevated venous pressures are not clear. Thompson et al [4]studied children with complex craniosynostosis using MR and subdural ICP monitoring and found a significant correlation between the presence of tonsillar herniation and increased ICP. Although Thompson et al [4]concluded venous hypertension was responsible for the raised ICP, venous pressures were not measured in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Chiari I malformation has been historically noted in patients with various forms of craniosynostosis [1, 2, 3, 4, 5, 6]. To our knowledge, metopic synostosis has not specifically been described as predisposing patients to cerebellar tonsillar ectopia.…”
Section: Introductionmentioning
confidence: 99%